IMPLEMENTASI GERAKAN MADRASAH INOVATIF MELALUI PENYELENGGARAAN MADRASAH ENTREPRENEUR DI MAN 1 JOMBANG - Masturi Masturi; Khoirul Umam (Universitas Islam Lamongan, 2022)
MAN 1 Jombang is one of the madrasas that implements the Innovative Madrasah Movement Program through the Let's Build Madrasah (GERAMM) movement, one of which is organizing entrepreneurial madrasas. The researcher aims to discuss the Entrepreneurial Madrasa at MAN 1 Jombang, focusing on the implementation process and the obstacles faced. This study uses a qualitative research type with a case study approach. The analysis results found that the entrepreneurial madrasa at MAN 1 Jombang was carried out through various entrepreneurship units, cooperatives, and waste banks. In addition, students are also taught to write scientific papers related to entrepreneurship and are often involved in expo activities. This has met the criteria for an entrepreneur madrasa launched by the Ministry of Religion of the East Java Region. Meanwhile, the obstacles faced in implementing entrepreneurial madrasas are still the uneven perception of students about entrepreneurship and the limited facilities and infrastructure to support entrepreneurship.